Ethanol, TLR3, and TLR4 Agonists Have Unique Innate Immune Responses in Neuron‐Like SH‐SY5Y and Microglia‐Like BV2. (30th March 2017) - Lawrimore, Colleen J.; Crews, Fulton T.
Abstract : Background: Ethanol (EtOH) consumption leads to an increase of proinflammatory signaling via activation of Toll‐like receptors (TLRs) such as TLR3 and TLR4 that leads to kinase activation (ERK1/2, p38, TBK1), transcription factor activation (NF κ B, IRF3), and increased transcription of proinflammatory cytokines such as TNF‐ α, IL‐1 β, and IL‐6. This immune signaling cascade is thought to play a role in neurodegeneration and alcohol use disorders. While microglia are considered to be the primary macrophage in brain, it is unclear what if any role neurons play in EtOH‐induced proinflammatory signaling. Methods: Microglia‐like BV2 and retinoic acid‐differentiated neuron‐like SH‐SY5Y were treated with TLR3 agonist Poly(I:C), TLR4 agonist lipopolysaccharide (LPS), or EtOH for 10 or 30 minutes to examine proinflammatory immune signaling kinase and transcription factor activation using Western blot, and for 24 hours to examine induction of proinflammatory gene mRNA using RT‐PCR. Results: In BV2, both LPS and Poly(I:C) increased p‐ERK1/2, p‐p38, and p‐NF κ B by 30 minutes, whereas EtOH decreased p‐ERK1/2 and increased p‐IRF3. LPS, Poly(I:C), and EtOH all increased TNF‐ α and IL‐1 β mRNA, and EtOH further increased TLR2, 7, 8, and MD‐2 mRNA in BV2. In SH‐SY5Y, LPS had no effect on kinase or proinflammatory gene expression. However, Poly(I:C) increased p‐p38 and p‐IRF3, and increased expression of TNF‐ α, IL‐1 β, and IL‐6, while EtOH increased p‐p38, p‐IRF3, p‐TBK1, and p‐NF κ B while decreasing p‐ERK1/2 and increasing expression of TLR3, 7, 8, and RAGE mRNA. HMGB1, a TLR agonist, was induced by LPS in BV2 and by EtOH in both cell types. EtOH was more potent at inducing proinflammatory gene mRNA in SH‐SY5Y compared with BV2. Conclusions: These results support a novel and unique mechanism of EtOH, TLR3, and TLR4 signaling in neuron‐like SH‐SY5Y and microglia‐like BV2 that likely contributes to the complexity of brain neuroimmune signaling. Abstract : This manuscript details the respective role of neuron‐like SH‐SY5Y and microglia‐like BV2 in ethanol‐induced innate immune signaling, and compares ethanol to either TLR3 or TLR4 activation. In BV2, both TLR3 and TLR4 activation increases downstream kinases and innate immune genes, while only TLR3 activation causes activation of kinases/innate immune genes in SH‐SY5Y. In both cell types, ethanol induces broader activation of kinases/innate immune genes. These results support a novel mechanism of ethanol‐induced signaling in both microglia‐like and neuron‐like cells.